2021
DOI: 10.1093/infdis/jiab147
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Infection Blocks Severe Acute Respiratory Syndrome Coronavirus 2 Replication Within the Respiratory Epithelium: Implications for COVID-19 Epidemiology

Abstract: Virus-virus interactions influence the epidemiology of respiratory infections. However, the impact of viruses causing upper respiratory infections on SARS-CoV-2 replication and transmission is currently unknown. Human rhinoviruses cause the common cold and are the most prevalent respiratory viruses of humans. Interactions between rhinoviruses and co-circulating respiratory viruses have been shown to shape virus epidemiology at the individual host and population level. Here, we examined the replication kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 22 publications
7
133
3
6
Order By: Relevance
“…Our findings may not only reflect changes in awareness and behavior associated with COVID-19. For example, viral interference, which is a phenomenon where one virus out-competes and suppresses the replication of other co-infecting viruses, may also be happening [40][41][42]. Certainly, the decrease in the number of children with many infectious diseases post-COVID-19 is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may not only reflect changes in awareness and behavior associated with COVID-19. For example, viral interference, which is a phenomenon where one virus out-competes and suppresses the replication of other co-infecting viruses, may also be happening [40][41][42]. Certainly, the decrease in the number of children with many infectious diseases post-COVID-19 is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have proposed mechanisms that could lead to a higher level of protection against SARS-CoV-2, we mention e.g. [9,17]. In a separate manuscript, we provide evidence of a protective effect by cross-reactive antibodies between a peptide in neuraminidace of Influenza A H1N1 and the binding domain the spike protein of SARS-CoV-2 that interacts with the angiotensin-converting enzyme 2 (ACE2), [18].…”
Section: Does Variable Susceptibility Exist?mentioning
confidence: 84%
“…Additionally, we assumed that interactions between viruses were neutral, meaning that the presence of one of the viruses did not affect (promote nor protect against) infection with the other virus. Recent studies have suggested some possible protection from COVID-19 infection conferred by rhinovirus interference with SARS-CoV-2 replication kinetics and this may warrant further exploration at the population level [33].…”
Section: Discussionmentioning
confidence: 99%